Global incidence of osteonecrosis of the femoral head after femoral neck fracture surgery in adolescents: a meta-analysis - Bangning Gu; Fangming Yao; Peng Peng; Zijun Zeng; Wei He; Qiushi Wei (Journal of Orthopaedic Surgery and Research)
Abstract Background Osteonecrosis of the femoral head (ONFH) is a significant postoperative complication following femoral neck fractures (FNFs) in adolescents, that has garnered considerable attention from researchers. Despite this interest, the incidence of ONFH in adolescents post-FNF surgery has not been extensively evaluated. To contribute to the body of research, we performed a meta-analysis utilizing articles sourced from multiple databases, with an emphasis on the rate of ONFH occurrence in young adolescents following FNF surgery. Objective The purpose of this study was to investigate the incidence of ONFH after FNFs in adolescents worldwide and analyse potential risk factors affecting its occurrence to provide guidance for the treatment and rehabilitation after FNFs in adolescents and reduce the incidence of ONFH. Methods A comprehensive search of medical literature databases, including MEDLINE, Web of Science, the Cochrane Library, and Embase, was conducted to identify relevant studies on ONFH and its associated risk factors after surgical treatment for FNFs in adolescents, covering the period from the establishment of the database to April 2024. Studies that did not meet the inclusion criteria were excluded. The study was conducted based on the preferred reporting items for systematic reviews and meta-analyses (PRISMA). Literature extraction, management, and data entry were performed using Zotero 6.0 and Excel 2016. The meta-analysis was conducted using R Studio 4.2.2. Subgroup analysis, sensitivity analysis, and assessment of publication bias were performed to explore sources of heterogeneity and evaluate the reliability of the results. This study has been registered on Prospero. (registration number: CRD4202452794; date of registration: 03/04/2024) Results A total of 17 publications involving 862 patients with FNFs were included in this meta-analysis. The findings revealed that the incidence of ONFH after FNF surgery in adolescents was 24.02% [95% CI (0.2118, 0.2712)]. The included studies demonstrated good consistency, and no publication bias was observed. Conclusion This study revealed that the incidence of ONFH after FNFs in adolescents is high (24.02%). Early screening and effective treatment of postoperative patients are crucial.